Genetic variability in Indian populations of banana corm weevil [Cosmopolites sordidus (Coleoptera: Curculionidae)] assessed by RAPDs and AFLPs. (17th August 2017) - Yadav, Sweta Kumari U.; Singh, Jyotsna; Padmanaban, B.; Kumar, Lalitha Sunil
Abstract: Cosmopolites sordidus (Germar), commonly known as banana corm weevil, is an important economic pest in Asia that can cause severe yield loss depending upon the stage at which infestation occurs. In spite of its economic importance, little is known about the population structure of this pest in India. Random amplified polymorphic DNA (RAPD) and amplified fragment length polymorphism (AFLP) were used to characterize the population genetic structure of C. sordidus collected from five hot spot locations in India. Nineteen RAPD primers and five selective AFLP primer combinations generated 147 and 304 amplification products, respectively. UPGMA dendrograms generated with both marker systems failed to reveal populations clustered based on geographic distance, which was confirmed by the Mantel test, which did not show a strong correlation between genetic distance and geographic distance. Values of indices of genetic identity showed that the populations were closely related. Though the gene flow estimate (Nm) between the populations was 0.469, suggesting restricted gene flow, the populations are not genetically distinct. These observations suggest that the range expansion of this banana pest in India has taken place through transport of infested corms and plant material, resulting in genetically close populations that are geographically distinct. These results provide important information on the population structure of this pest in India, which will aid in designing suitable strategies for its control and management, especially with respect to insecticide resistance.